Rapid heat discharge during deep-sea eruptions generates megaplumes and disperses tephra - Samuel S. Pegler (Nature Portfolio, 2021)
A novel model for submarine tephra dispersal by hydrothermal megaplumes is proposed. The energy flux inferred from our model aligns with megaplume observations, and suggests that the catastrophic release of hot crustal fluids, as opposed to lava heating, is responsible for megaplume generation.